Crematory and Mash Systems, The Sole Nexus of the Sexual Component of the Innate Bisexuality - Pirot, Florent; Mezhennaya, Maria; Lavin, Claire (European Journal of Applied Sciences, 2025)
This paper shows the direct and definitive link between crematory and mash systems and the sexual component of bisexuality. The innate bisexuality was earlier defined as an affective concept. The sexual component is related to crematory and mash contamination, in particular, as well as crematory and mash antigravitons. This is shown through a varsity of ways.